2007
DOI: 10.1111/j.1365-2265.2007.03099.x
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant alpha‐lipoic acid improves endothelial dysfunction induced by acute hyperglycaemia during OGTT in impaired glucose tolerance

Abstract: In subjects with IGT, FMD was impaired both in the fasting state and after a glucose challenge, probably through increased production of oxygen-derived free radicals. The ED observed after a glucose challenge is related to the extent of hyperglycaemia and TBARS, and an antioxidant agent can improve the impairment of endothelial function induced by acute hyperglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 37 publications
6
44
1
Order By: Relevance
“…Consistent with these experimental data, there is evidence that oral supplementation of ALA decreases oxidative stress in diabetic patients as assessed by measurement of plasma lipid hydroperoxides [9]. A recent study in patients with impaired glucose tolerance showed beneficial effects of short-term ALA (300 mg) on endothelial function [22].…”
Section: Discussionsupporting
confidence: 67%
“…Consistent with these experimental data, there is evidence that oral supplementation of ALA decreases oxidative stress in diabetic patients as assessed by measurement of plasma lipid hydroperoxides [9]. A recent study in patients with impaired glucose tolerance showed beneficial effects of short-term ALA (300 mg) on endothelial function [22].…”
Section: Discussionsupporting
confidence: 67%
“…For instance, Kawano et al (54) observed significant postprandial elevations in TBARS and attenuated flow-mediated dilatation of the brachial artery following an OGTT in subjects with IGT and T2DM while healthy controls were not significantly affected by such challenge. Xiang et al (53) observed similar findings in subjects with IGT and, like Kawano et al (54) , observed a positive correlation between postprandial oxidative stress and endothelial dysfunction.…”
Section: Pathophysiology Of Oxidative Stresssupporting
confidence: 70%
“…Previous studies have established that oxygen-derived free radicals interfere with or destroy FMD by inactivating NO in normal vessels [21,22]. Recently, some studies have documented that plasma TBARS, a marker of oxygen-derived free radicals, is negatively related to the FMD of the brachial conduit artery [18,23]. In the present study, we found that the TBARS levels increase markedly at Day 1 after CMR, which is inversely associated with FMD during the follow-up days.…”
Section: Discussionsupporting
confidence: 45%